2020
DOI: 10.1016/j.eng.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Treatment with Favipiravir for COVID-19: An Open-Label Control Study

Abstract: a b s t r a c tAn outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and its caused coronavirus disease 2019 has been reported in China since December 2019. More than 16% of patients developed acute respiratory distress syndrome, and the fatality ratio was about 1%-2%. No specific treatment has been reported. Herein, we examine the effects of Favipiravir (FPV) versus Lopinavir (LPV)/ritonavir (RTV) for the treatment of COVID-19. Patients with laboratory-confirmed COVID-19 who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
1,189
11
77

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,195 publications
(1,334 citation statements)
references
References 15 publications
10
1,189
11
77
Order By: Relevance
“…A clinical trial to evaluate the safety and efficacy of favipiravir in the treatment of COVID-19 (ChiCTR2000029600) was conducted in Shenzhen, with 80 patients recruited. 11 The results showed that the 35 patients in the favipiravir arm demonstrated significantly shorter viral clearance time as compared with the 45 patients in the control arm (median 4 days vs. 11 days). X-ray examinations confirmed a higher rate of improvement in chest imaging in the favipiravir arm (91.43% vs. 62%).…”
Section: Antiviral Treatment For Covid-19 and Potential Use Of Favipimentioning
confidence: 93%
“…A clinical trial to evaluate the safety and efficacy of favipiravir in the treatment of COVID-19 (ChiCTR2000029600) was conducted in Shenzhen, with 80 patients recruited. 11 The results showed that the 35 patients in the favipiravir arm demonstrated significantly shorter viral clearance time as compared with the 45 patients in the control arm (median 4 days vs. 11 days). X-ray examinations confirmed a higher rate of improvement in chest imaging in the favipiravir arm (91.43% vs. 62%).…”
Section: Antiviral Treatment For Covid-19 and Potential Use Of Favipimentioning
confidence: 93%
“…For example, 199 patients in a clinical future science group www.future-science.com study conducted in Jin Yin-Tan Hospital, received a supportive therapy of supplemental oxygen, noninvasive and invasive ventilation, antibiotics, vasopressor support, renal-replacement therapy and extracorporeal membrane oxygenation (ECMO) [72]. Another clinical study at the national clinical research center for infectious diseases (the Third People's Hospital of Shenzhen), Shenzhen, China, has reported the use of oxygen inhalation, oral or intravenous rehydration therapy, electrolyte correction, antipyretics, analgesics and antiemetic drugs as supportive therapy for the patient [73]. Another example of supportive care is what is given to the first diagnosed case of SARS-CoV-2 in Washington, USA.…”
Section: Current Treatments Adapted To Manage the Diseasementioning
confidence: 99%
“…It blocks the replication of several viruses other than influenza. [73]. Therefore, FPV stands as a promising agent in the management of SARS-CoV-2.…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…With regard to favipiravir, an RCT 25 in 236 patients with mixedseverity COVID-19 suggested, in comparison with umifenovir, a possible higher incidence of recovery at day 7, but because of risk of bias, imprecision and indirectness, the evidence was only very low quality (Appendix 3). 22 One observational study 26 in 80 patients with nonsevere COVID-19 provides very low-quality evidence that favipiravir may increase viral clearance at day 7 relative to lopinavir-ritonavir. Symptomatic benefit outcomes from patients with nonsevere disease for other agents were unavailable.…”
Section: Antiviral Drugsmentioning
confidence: 99%